THER-34. MEK BLOCKADE SYNERGISTICALLY INCREASES THE ANTI-TUMOR EFFECTS OF mTOR INHIBITION IN GLIOMAS. (23rd April 2019) - Zhang, Jie; Liu, Kevin; Dik, Rogier; Yang, Xiaodong; Waanders, Angela; Resnick, Adam; Wright, Karen; Weiss, William; Haas-Kogan, Daphne; Mueller, Sabine
Abstract: Abnormal signaling of the RAS/RAF and mTOR pathways predominates in pediatric low-grade gliomas (PLGGs). MLN0128 is a second-generation pan-mTOR inhibitor (TORC1/2). Rapalink-1, a third-generation bivalent mTOR inhibitor that combines rapamycin with MLN0128 by an inert chemical linker, shows potent anti-tumor effects in preclinical adult glioma models. MEK inhibition with e.g. AZD6244 shows promising anti-tumor effects in PLGGs and the type II generation pan-RAF inhibitor TAK580 is currently under clinical investigation in PLGG. In this study, we evaluate the effects of MLN0128 and Rapalink-1 in preclinical models of PLGGs, for both mono- and combination therapy with AZD6244 and TAK580. These inhibitors were used to treat glioma cell lines carrying wild-type BRAF (SF188 and LN229), and isogenic systems of KIAA1549-BRAF expressing NIH/3T3 cell line. Using CellTiter-Glo Luminescent Cell Viability Assay, we found that mTOR inhibition monotherapy reduces cell viability in a dose dependent manner while Rapalink-1 (IC50 between 3.5–8.2nM) is more effective than MLN0128 (IC50 between 22.9–120.2nM). Combined with AZD6244, both inhibitors synergistically increase the suppression of cell viability (combination index value nd generation pan-RAF inhibitor TAK580 in combination with mTOR inhibition.